A kind of non-floating fiber easy demoulding reinforced PA6 material and preparation method thereof
By adding components such as short -cut glass fiber, MXD6 nylon resin, and crystalline inhibitory mother grains to the PA6 material, the problem of floating fiber and difficulty in the pyramid fiber in the injection molding system of the glass fiber is solved. The effect of the mold removal improves the appearance quality and production efficiency of the parts.
Patent Information
- Application Number
- CN202311521930.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-15
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-11-15
AI Technical Summary
Existing glass fiber reinforced PA6 materials are prone to floating fibers in injection molded parts and are difficult to release, which affects the appearance aesthetics and production efficiency of the parts.
Composite materials such as PA6 resin, short -cut glass fiber, MXD6 nylon resin, and crystalline inhibit maternal particles are used to prepare a enhanced PA6 material without floating fiber -free and easy -to -mold through the mixing, extrusion and granularity process. Crystal inhibits the mother grains contain nylon resin, polyethylene pyrodidone, and chlorine -containing compounds. It can reduce the crystallinity of PA6, reduce the cooling speed of the material, and prevent floating fiber.
The floating fibrous fiber -free and easy molding effect of the PA6 material has improved the surface smoothness and luster of the parts, reducing production costs, and expanding the application range of the material in the structural parts.
Smart Images

Figure BDA0004550795970000061 
Figure BDA0004550795970000071 
Figure BDA0004550795970000081
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polymer composite materials, and more specifically, to a non-floating fiber, easy-to-demold reinforced PA6 material and a preparation method thereof. Background Art
[0002] Polyamide 6 (PA6, also known as nylon 6) is a crystalline thermoplastic engineering plastic with good toughness, chemical resistance, self-lubrication and other advantages. However, as a structural part, polyamide 6 is limited in its scope of use due to its high hygroscopicity, high creep, low heat resistance, high molding shrinkage, and poor dimensional stability. Modification with glass fiber can greatly improve the above shortcomings and expand its scope of use.
[0003] Generally speaking, the tensile strength and flexural strength of PA6 after glass fiber reinforcement and modification can be increased by 2 to 3 times, the flexural modulus can be increased by 2 to 5 times, and the creep resistance is reduced to one-fourth or even lower than that of unreinforced PA6. However, glass fiber reinforced PA composite materials are difficult to process, mainly because the glass fiber has a small diameter and lacks active groups on the surface. PA cannot be fully impregnated when in contact with glass fiber. The glass fiber is exposed to the surface during the flow of plastic melt filling the mold, and after condensation and molding, radial white marks are formed on the surface of the plastic part. When the plastic part is black, the color difference will be more obvious, causing defects such as glass fiber exposure, product sticking film, inability to demold, and very rough internal and external surfaces in PA6 parts, which affects the appearance of PA6 parts.
[0004] With the continuous development of science and technology and the continuous improvement of human needs, not only are material properties required to meet standards, but also the appearance of injection molded parts is required to be good, such as no floating fiber phenomenon, reducing the decoration or painting process, saving costs, such as bus seat frame backrest, engine hood, rearview mirror bracket, etc. In view of the above-mentioned related technologies, research on a glass fiber reinforced PA6 material without floating fibers and easy demoulding has broad application prospects. Summary of the invention
[0005] In order to improve the floating fiber phenomenon of glass fiber reinforced PA6 injection molded parts and enhance the demoulding effect, the present application provides a non-floating fiber easy-to-demold reinforced PA6 material and a preparation method thereof.
[0006] In the first aspect, the present application provides a non-floating fiber easy-to-demold reinforced PA6 material, which adopts the following technical scheme: a non-floating fiber easy-to-demold reinforced PA6 material, comprising the following raw materials in parts by weight: 26.7-72.1 parts of PA6 resin, 20-50 parts of chopped glass fiber, 5-15 parts of MXD6 nylon resin, 0.4-0.8 parts of compounded antioxidant, 0.5-1.5 parts of lubricant, and 2-6 parts of crystallization inhibition masterbatch;
[0007] The crystallization inhibiting masterbatch comprises the following raw materials in parts by weight: 60.6-64.5 parts of nylon resin, 4-5 parts of chlorine-containing compounds, 30-35 parts of polyvinyl pyrrolidone and 0.4-0.5 parts of compound antioxidant, wherein the chlorine-containing compounds are lithium chloride and / or calcium chloride.
[0008] By adopting the above technical scheme, PA6 resin is used as the main base material, short-cut glass fiber is added as a reinforcing material, and components such as MXD6 nylon resin and crystallization-inhibiting masterbatch are added. Short-cut glass fiber can be used as the skeleton of the material in the PA6 material to effectively transfer stress, improve the stiffness, strength and hardness of the product, and also has a certain toughening effect, can reduce friction, resist wear, and increase the dimensional stability of the product. MXD6 nylon resin is a semi-crystalline aromatic polymer formed by the condensation of metaphenylenediamine and adipic acid. It has the characteristics of high strength, good heat resistance, low shrinkage and excellent barrier properties. It is a special high-barrier nylon material with weak crystallinity, which can reduce the crystallinity of PA6. In addition, it can also reduce the water absorption of the material and improve the strength of the material. In the crystallization-inhibiting masterbatch, nylon resin is used as a compatibilizer. To increase the dispersibility of chlorine-containing compounds and PA6 resin matrix, lithium chloride or calcium chloride as chlorine-containing compounds can inhibit the crystallization of PA6 materials, because the complex reaction of lithium chloride or calcium chloride with PA6 resin destroys the hydrogen bonds between PA6 molecules, and the formation of complexes seriously restricts the movement of PA6 molecular chains, making PA6 difficult to crystallize. The carbonyl group in polyvinyl pyrrolidone can form intermolecular hydrogen bonds with NH on the main chain of PA6 resin. The formation of intermolecular hydrogen bonds affects the crystallization process of PA6 resin and reduces the crystallinity. The compounding of MXD6 nylon resin and crystallization inhibition masterbatch will not only effectively reduce the crystallinity of PA6 materials, thereby reducing the cooling rate of the material on the mold surface, so that the chopped glass fibers will not be quickly rushed to the surface of the part to form floating fibers, but also improve the mechanical strength.
[0009] Optionally, the chlorine-containing compound includes calcium chloride and lithium chloride in a mass ratio of 1:0.8-1. By adopting the above technical solution, a mixture of calcium chloride and lithium chloride is added to the PA6 resin, and the complex coordination effect of the metal ions and the amide groups destroys the hydrogen bond structure in the PA6 molecules that helps to arrange the molecules regularly. In addition, this complexation forms multiple ligands, so that several molecular chains are cross-linked together to form a chain end restricted structure similar to the dispersed phase in the blending system, which makes it difficult for the PA6 chain segments to move, and the molecular chains are not easy to be arranged into the crystal lattice, further hindering crystallization.
[0010] Optionally, the crystallization inhibiting masterbatch is prepared by the following method: drying the nylon resin, mixing it with a chlorine-containing compound, polyvinyl pyrrolidone and a compound antioxidant, and extruding and granulating it at 190-235°C.
[0011] By adopting the above technical scheme, nylon resin is mixed with chlorine-containing compounds, polyvinyl pyrrolidone and other components for extrusion and granulation. The prepared crystallization inhibition masterbatch can reduce the crystallinity of PA6 resin, improve the cooling speed of PA6 material on the mold surface, and reduce the floating fiber phenomenon.
[0012] Optionally, the mass ratio of the MXD6 nylon resin to the crystallization inhibition masterbatch is 2-2.5:1.
[0013] By adopting the above technical solution, the MXD6 nylon resin and crystallization inhibition masterbatch in the above mass ratio can more effectively inhibit the crystallinity of the PA6 material, reduce its cooling rate on the mold, and prevent floating fibers.
[0014] Optionally, the viscosity of the PA6 resin is 2.2-2.5, and the viscosity of the MXD6 nylon resin is 2.45-2.7.
[0015] By adopting the above technical solution, the viscosity of PA6 resin is lower than that of MXD6 nylon resin, and the melting point of MXD6 nylon resin is about 20°C higher than that of PA6. When PA6 resin is hot-melted, MXD6 nylon resin is not completely hot-melted, and MXD6 nylon resin has high viscosity and poor fluidity. During blending and injection molding, MXD6 nylon resin can hold the chopped glass fiber, so that PA6 resin quickly forms a coating on the mold surface, which can better wrap the fiber in the resin, play a role in preventing floating fibers, and make the surface of PA6 material smoother, with high surface gloss and easy demoulding.
[0016] Optionally, the chopped glass fibers are pretreated as follows:
[0017] The chopped glass fibers are immersed in an aqueous solution of a silane coupling agent, taken out, and dried to obtain pretreated chopped glass fibers;
[0018] Dissolving polyvinylidene fluoride in a solvent to obtain a solution with a concentration of 50-55 wt%, adding a hyperdispersant and nano-silicon dioxide, and performing ultrasonic homogenization to obtain a blended liquid;
[0019] The blended liquid is evenly sprayed on the pre-treated chopped glass fibers and dried.
[0020] By adopting the above technical scheme, the short glass fibers are first pretreated with a silane coupling agent. The molecular structure of the silane coupling agent contains a silicon-oxygen bond and an organic group. The silicon-oxygen bond can react with the hydroxyl group on the surface of the short glass fibers to form a chemical bond, and the organic group can form a physical bond with polyvinylidene fluoride, thereby improving the surface morphology and activity of the short glass fibers, increasing their wettability, increasing their surface roughness, and increasing their mechanical anchoring force and chemical bond binding force with polyvinylidene fluoride. After the blended liquid formed by polyvinylidene fluoride, a hyperdispersant and nano-silica is sprayed on the short glass fibers treated with the coupling agent, the polar groups contained in the hyperdispersant can generate a strong attraction with the long chain ends of the silane coupling agent on the surface of the short glass fibers through van der Waals forces, thereby The phase interface is eliminated, so that the hyperdispersant and the chopped glass fiber form one phase, and the solvated chain segments in the hyperdispersant have a certain compatibility with the PA6 matrix, forming similar anchor nodes, i.e., cross-linking points, in PA6 resin and MXD6 nylon resin parts, which enhances the bonding strength between the glass fiber and the PA6 fiber, thereby improving the tensile strength and impact strength, and improving the wettability of the SMS glass fiber. Under the adhesion of polyvinylidene fluoride, nano-silica is evenly adhered to the chopped glass fiber. The shape of the nano-silica is spherical and the surface is smooth. It adheres to the rough surface of the chopped glass fiber pretreated with a silane coupling agent, reduces the surface roughness of the chopped glass fiber, improves its surface smoothness and density, and improves the gloss of the PA6 material.
[0021] Optionally, when pretreating the chopped glass fibers, the weight proportions of the raw materials are as follows: 40-50 parts of chopped glass fibers, 40-50 parts of an aqueous solution of a silane coupling agent, 5-10.5 parts of polyvinylidene fluoride, 3-6 parts of a hyperdispersant, and 4-8 parts of nano-silicon dioxide.
[0022] By adopting the above technical scheme, the above amounts of raw materials can increase the wettability of the chopped glass fibers, improve their dispersibility in the PA6 resin, and enhance their surface smoothness and density, thereby reducing floating fibers and improving glossiness.
[0023] Optionally, the lubricant is selected from at least one of silicone powder, modified ethylene bisstearamide and calcium stearate.
[0024] By adopting the above technical solution, silicone powder, calcium stearate and modified ethylene bisstearamide as lubricants can reduce the friction and shear between polymer materials such as PA6 resin and metal mold wall parts, and improve the uniformity of material flow, demoulding effect and extrusion quality.
[0025] Optionally, the lubricant comprises silicone powder and modified ethylene bisstearamide in a mass ratio of 1:0.875-1.
[0026] By adopting the above technical scheme, silicone powder and modified ethylene bis stearamide are used as lubricants, which can further improve the fluidity of the material, reduce the friction between the physical and the mold, improve the demoulding effect, and improve the surface smoothness of the composite material. In addition, the modified ethylene bis stearamide contains a polar group structure that can combine with some polar groups on the surface of the short glass fiber. In the glass fiber reinforced or inorganically filled PA6 system, a similar anchoring node is formed between the short glass fiber and the PA6 resin, thereby improving the bonding state between the short glass fiber and the PA6 resin and improving the dispersibility in the PA6 resin.
[0027] Optionally, the compound antioxidant includes antioxidant 1098 and antioxidant 168 in a mass ratio of 2-2.5:1.
[0028] By adopting the above technical solution and using antioxidant 1098 and antioxidant 168 as compound antioxidants, the aging resistance and UV resistance of PA6 materials can be improved, and yellowing or cracking of products due to oxidation can be avoided.
[0029] In the second aspect, the present application provides a method for preparing a non-floating fiber easy-to-release reinforced PA6 material, which adopts the following technical solution:
[0030] A method for preparing a non-floating fiber easy-to-release reinforced PA6 material, comprising the following steps:
[0031] The PA6 resin, MXD6 nylon resin, compound antioxidant, lubricant and crystallization inhibition masterbatch are mixed evenly, and the short-cut glass fiber is added from the side feeding port. After blending, extrusion, granulation and vacuum drying, the floating fiber-free and easy-to-demold reinforced PA6 material is obtained.
[0032] By adopting the above technical solution, the remaining raw materials except the chopped glass fibers are blended, and the chopped glass fibers are added through the side feeding port, which can facilitate the uniform blending of the chopped glass fibers and the matrix resin, etc., and reduce the floating fiber phenomenon.
[0033] In summary, this application has the following beneficial effects:
[0034] 1. Since the present application adopts PA6 resin, MXD6 nylon resin and crystallization inhibiting masterbatch and other components to prepare PA6 material, the crystallization inhibiting masterbatch contains nylon resin, polyvinyl pyrrolidone and chlorine-containing compounds (lithium chloride and / or calcium chloride), the compounding of crystallization inhibiting masterbatch and MXD6 can limit the movement of PA6 molecular chains and reduce the crystallinity of PA6 resin, thereby reducing the cooling rate of PA6 material on the mold surface, making it difficult for short chopped glass fibers to be quickly rushed to the surface of the workpiece to form floating fibers, thereby making a PA6 material with no floating fibers on the surface and easy demolding.
[0035] 2. In this application, MXD6 nylon resin with a viscosity greater than that of PA6 resin is used, and the melting point of MXD6 nylon resin is higher than that of PA6 resin. During injection molding, PA6 resin flows after being completely melted, while MXD6 that is not completely melted has a larger viscosity and a slower fluidity, which can hold the chopped glass fibers, allowing the PA6 resin to quickly form a coating on the mold surface, thereby better encapsulating the chopped glass fibers and achieving a better anti-floating fiber effect.
[0036] 3. In the present application, it is preferred to use a blended liquid formed by polyvinylidene fluoride, a hyperdispersant and nano-silica to spray the chopped glass fibers pretreated with a silane coupling agent, so that the wettability of the chopped glass fibers is improved, and the surface smoothness and density are improved, thereby improving the surface smoothness and glossiness of the product. DETAILED DESCRIPTION
[0037] Preparation Example 1-6 of Crystallization Inhibiting Masterbatch
[0038] Preparation Example 1: 64.5 g of nylon resin after drying (120°C, drying for 4 hours) was mixed with 5 g of chlorine-containing compound, 30 g of polyvinyl pyrrolidone and 0.5 g of compound antioxidant, and added to the main feeding port of the extruder. After melting, extrusion, granulation and drying, a crystallization inhibition masterbatch was obtained. The chlorine-containing compound included calcium chloride and lithium chloride in a mass ratio of 1:1, the compound antioxidant included antioxidant 1098 and antioxidant 168 in a mass ratio of 2:1, and the nylon resin The viscosity is 2.45, selected from Haiyang Technology Co., Ltd., model is HY2500A, the polyvinyl pyrrolidone model is K30, the extruder screw speed is 350rpm, the temperature of zone 1 is 190℃, the temperature of zone 2 is 200℃, the temperature of zone 3 is 220℃, the temperature of zone 4 is 220℃, the temperature of zone 5 is 230℃, the temperature of zone 6 is 225℃, the temperature of zone 7 is 230℃, the temperature of zone 8 is 230℃, the temperature of zone 9 is 235℃, and the temperature of zone 10 is 235℃.
[0039] Preparation Example 2: 60.6 g of nylon resin after drying (120°C, drying for 4 hours) was mixed with 4 g of chlorine-containing compound, 35 g of polyvinyl pyrrolidone and 0.4 g of compound antioxidant, and added to the main feeding port of the extruder. After melting, extrusion, granulation and drying, a crystallization inhibition masterbatch was obtained. The chlorine-containing compound included calcium chloride and lithium chloride in a mass ratio of 1:0.8, the compound antioxidant included antioxidant 1098 and antioxidant 168 in a mass ratio of 2:1, and the nylon resin The viscosity is 2.45, selected from Haiyang Technology Co., Ltd., model is HY2500A, the polyvinyl pyrrolidone model is K30, the extruder screw speed is 350rpm, the temperature of zone 1 is 190℃, the temperature of zone 2 is 200℃, the temperature of zone 3 is 220℃, the temperature of zone 4 is 220℃, the temperature of zone 5 is 230℃, the temperature of zone 6 is 225℃, the temperature of zone 7 is 230℃, the temperature of zone 8 is 230℃, the temperature of zone 9 is 235℃, and the temperature of zone 10 is 235℃.
[0040] Preparation Example 3: The difference from Preparation Example 1 is that the chlorine-containing compound is calcium chloride.
[0041] Preparation Example 4: The difference from Preparation Example 1 is that the chlorine-containing compound is lithium chloride.
[0042] Preparation Example 5: The difference from Preparation Example 1 is that no chlorine-containing compound is added.
[0043] Preparation Example 6: The difference from Preparation Example 1 is that polyvinyl pyrrolidone is not added.
[0044] Example
[0045] Example 1: A non-floating fiber easy demoulding reinforced PA6 material, the raw material ratio (in kg) is shown in Table 1. The viscosity of the PA6 resin in Table 1 is 2.45, selected from Haiyang Technology Co., Ltd., model HY2500A, the relative viscosity of the MXD6 nylon resin is 2.65, and the specific gravity is 1.22 g / cm 3 , the melt index is 2g / 10min, selected from Mitsubishi Gas Chemical Co., Ltd., model ME1007, the crystallization inhibition masterbatch is made from Preparation Example 1, the length of the chopped glass fiber is 3mm, the diameter is 10μm, selected from China Jushi Co., Ltd., model 568H, the compound antioxidant includes antioxidant 1098 and antioxidant 168 in a mass ratio of 2:1, and the lubricant is modified ethylene bisstearamide, selected from Suzhou Xingtai Guoguang Chemical Additive Co., Ltd.
[0046] The preparation method of the above-mentioned non-floating fiber easy-to-release reinforced PA6 material comprises the following steps:
[0047] The PA6 resin, MXD6 nylon resin, compound antioxidant, lubricant and crystallization inhibition masterbatch are mixed evenly, and the short glass fiber is added from the side feeding port. After blending, extrusion, granulation, vacuum drying and injection molding, the screw speed is 250r / min, the vacuum drying temperature is 120℃, and the temperature of each zone during extrusion is as follows: the temperature of zone 1 is 190℃, the temperature of zone 2 is 190℃, the temperature of zone 3 is 230℃, the temperature of zone 4 is 230℃, the temperature of zone 5 is 250℃, the temperature of zone 6 is 240℃, the temperature of zone 7 is 220℃, the temperature of zone 8 is 220℃, the temperature of zone 9 is 220℃, and the temperature of zone 10 is 220℃, so as to obtain a reinforced PA6 material without floating fibers and easy to demold.
[0048] Table 1 Ratio of raw materials for non-floating fiber easy demoulding reinforced PA6 materials in Examples 1-6
[0049]
[0050] Example 2: A reinforced PA6 material without floating fibers and easy to demold. The difference from Example 1 is that the lubricant includes silicone powder and modified ethylene bisstearamide in a mass ratio of 1:1, and the silicone powder is selected from Chengdu Silike Technology Co., Ltd. and the model is LYSI-100.
[0051] Example 3-6: A non-floating fiber and easy-to-demold reinforced PA6 material, which is different from Example 1 in that the amounts of raw materials used are as shown in Table 1.
[0052] Example 7: A reinforced PA6 material without floating fibers and easy to demould, which differs from Example 4 in that the crystallization inhibiting masterbatch is made from Preparation Example 3.
[0053] Example 8: A floating fiber-free and easily demouldable reinforced PA6 material, which differs from Example 4 in that the crystallization-inhibiting masterbatch is made from Preparation Example 4.
[0054] Example 9: A non-floating fiber and easy-to-release reinforced PA6 material, which is different from Example 4 in that the chopped glass fibers are pretreated as follows:
[0055] 50 kg of chopped glass fibers were immersed in 50 kg of an aqueous solution of silane coupling agent KH550 with a concentration of 2.5 wt %, taken out, and dried to obtain pretreated chopped glass fibers;
[0056] 10.5 kg of polyvinylidene fluoride was dissolved in N, N-dimethylformamide to obtain a solution with a concentration of 55 wt%, 6 kg of a hyperdispersant and 8 kg of nano-silicon dioxide were added, and ultrasonic homogenization was performed to obtain a blended liquid, wherein the polyvinylidene fluoride was selected from Solvay of the United States, model 6010, the hyperdispersant model was Lubrizol 17000, and the silicon dioxide was fumed silicon dioxide, selected from Rhein Chemie, model Wacker HDK H15;
[0057] The blended liquid is evenly sprayed on the pre-treated chopped glass fibers and dried.
[0058] Example 10: A non-floating fiber and easy-to-release reinforced PA6 material, which is different from Example 4 in that the chopped glass fibers are pretreated as follows:
[0059] 40 kg of chopped glass fibers were immersed in 40 kg of an aqueous solution of silane coupling agent KH550 with a concentration of 2.5 wt %, taken out, and dried to obtain pretreated chopped glass fibers;
[0060] 5 kg of polyvinylidene fluoride was dissolved in N, N-dimethylformamide to obtain a solution with a concentration of 50 wt%, 3 kg of a hyperdispersant and 4 kg of nano-silicon dioxide were added, and ultrasonic homogenization was performed to obtain a blended liquid, wherein the polyvinylidene fluoride was selected from Solvay of the United States, model 6010, the hyperdispersant model was Lubrizol 17000, and the silicon dioxide was fumed silicon dioxide, selected from Rhein Chemie, model Wacker HDK H15;
[0061] The blended liquid is evenly sprayed on the pre-treated chopped glass fibers and dried.
[0062] Example 11: A reinforced PA6 material without floating fibers and easy to demould, which is different from Example 10 in that no nano-silicon dioxide is added to the blending liquid.
[0063] Example 12: A floating fiber-free and easily demouldable reinforced PA6 material, which differs from Example 10 in that no hyperdispersant is added to the blending liquid.
[0064] Example 13: A floating fiber-free and easily demouldable reinforced PA6 material, which differs from Example 10 in that an equal amount of water is used to replace the blending liquid.
[0065] Example 14: A floating fiber-free and easily demouldable reinforced PA6 material, which differs from Example 10 in that the chopped glass fibers are not pretreated with a silane coupling agent.
[0066] Comparative Example
[0067] Comparative Example 1-7: A PA6 material without floating fibers and easy demoulding, which is different from Example 1 in that the raw material ratio (in kg) is as shown in Table 2.
[0068] Table 2 Ratio of raw materials for non-floating fiber easy demoulding reinforced PA6 materials in comparative examples 1-7
[0069]
[0070]
[0071] Comparative Example 8: A reinforced PA6 material without floating fibers and easy to demold, which differs from Example 1 in that the crystallization inhibiting masterbatch is made from Preparation Example 5.
[0072] Comparative Example 9: A reinforced PA6 material without floating fibers and easy to demold, which differs from Example 1 in that the crystallization-inhibiting masterbatch is made from Preparation Example 6.
[0073] Example 10: A PA6 material without floating fibers and easy demoulding. The difference from Example 4 is that the PA6 resin is selected from Baling Petrochemical, the model is BL3280H, and the relative viscosity is 2.8.
[0074] Comparative Example 11: A warping-resistant glass fiber reinforced nylon material, composed of the following components: 40 parts of nylon 66; 30 parts of glass fiber; 5 parts of urea-formaldehyde resin; 20 parts of biotite, a mineral filler; 5 parts of acidic high-temperature ionic liquid, the viscosity of nylon is medium viscosity, and its relative viscosity range is 2.45-2.8, and the anion in the acidic high-temperature ionic liquid is BF 4 - .
[0075] The preparation process of the above-mentioned anti-warping glass fiber reinforced nylon material is as follows:
[0076] S1. After surface treatment of the glass fiber, ultrasonic treatment, cleaning and drying are performed; the surface treatment is to immerse the glass fiber in 20% hydrofluoric acid for 3 hours, and the glass fiber is selected to have a low orientation glass fiber with an elliptical cross section.
[0077] S2. Mix nylon 66, urea-formaldehyde resin, mineral filler and additives and place them in a twin-screw extruder. At the same time, add surface-treated glass fiber from the feed port and perform injection molding to obtain the anti-warping glass fiber reinforced nylon material. The process control conditions of the twin-screw extruder used in the preparation process are: 230° C. in zone 1, 230° C. in zone 2, 235° C. in zone 3, 235° C. in zone 4, 240° C. in zone 5, 240° C. in zone 6, 240° C. in zone 7, 240° C. in zone 8, 240° C. in zone 9 and 240° C. in zone 10; the residence time is 2 min and the pressure is 12 MPa.
[0078] Performance testing
[0079] PA6 material was prepared according to the methods in the examples and comparative examples, and performance tests were performed according to the following methods. The test results are recorded in Table 3.
[0080] 1. Density: Test in accordance with GB / T1033-1986 "Test method for density and relative density of plastics";
[0081] 2. Tensile strength: Tested in accordance with GB / T1040-1992 "Test method for tensile properties of plastics";
[0082] 3. Bending strength: Tested in accordance with GB / T9341-2008 "Determination of Bending Properties of Plastics";
[0083] 4. Izod notch impact strength: Tested in accordance with GB / T1843-2008 "Determination of plastic cantilever beam impact strength";
[0084] 5. Whether there are floating fibers on the surface and whether it is easy to demold: Add 1.5% of Cabot 2014 black masterbatch to the prepared PA6 material, mix well, and injection mold into a color plate with a length of 120mm×120mm×2.5mm. The injection molding temperature range is 230-270℃, and the mold temperature is 70℃. Observe the surface effect and the stickiness.
[0085] 6. Gloss: Test in accordance with GB / T8807-1988 "Test method for mirror gloss of plastics", using 60° angle lighting and detection signal.
[0086] Table 3 Performance test results of PA6 materials without floating fibers and easy demoulding
[0087]
[0088]
[0089] Combining Examples 1-6 and the data in Table 3, it can be seen that in Examples 1-4, as the amount of chopped glass fiber increases, the mechanical strength of the PA6 material gradually increases, and the appearance and demolding properties are also good. In Examples 4-6, with the same content of chopped glass fiber, the performance of Example 4 and Example 5 is basically similar. In Example 6, the amount of MXD6 nylon resin used is relatively small, which causes various properties to decline.
[0090] Compared with Example 4, Examples 7 and 8 respectively use only calcium chloride and lithium chloride as chlorine-containing compounds and add them to the crystallization inhibitor. The PA6 materials prepared in Examples 7 and 8 have excellent properties.
[0091] In Example 9 and Example 10, the chopped glass fibers were pretreated, and the tensile strength, bending strength and impact resistance of the PA6 materials obtained were improved, there was no floating fiber on the surface, it was still easier to demold, and the surface glossiness was improved.
[0092] In Example 11, when pre-treating the chopped glass fibers, no silica was added. Compared with Example 7, the mechanical strength such as the tensile strength of the PA6 material in Example 11 decreased, and the surface glossiness decreased.
[0093] Compared with Example 10, in Example 12, no hyperdispersant was added during the pretreatment of the chopped glass fibers. The mechanical strength of the PA6 material prepared in Example 12 did not change much, but the surface glossiness was reduced.
[0094] In Example 13, the blending liquid for pre-treating the chopped glass fibers was replaced with water. Compared with Example 10, the performance of the prepared PA6 material was similar to that of Example 4.
[0095] In Example 14, the chopped glass fibers were not pretreated with a coupling agent, and it can be seen that the tensile strength and impact strength of the PA6 material decreased, and the glossiness was reduced.
[0096] In Comparative Example 1, when MXD6 nylon resin and crystallization inhibiting masterbatch were not added, although the content of chopped glass fibers was low, floating fibers still existed. In Comparative Example 7, only the crystallization inhibiting masterbatch was not added, floating fibers occurred, and demolding was still easy.
[0097] In Comparative Examples 2 and 3, the compounding ratios of MXD6 nylon resin and crystallization inhibiting masterbatch are 10:1 and 4:6 respectively. The inappropriate compounding ratios result in floating fibers on the surface of the PA6 material, but it is easier to demold; in Comparative Example 4, the amount of MXD6 nylon resin used is too large, and in Comparative Example 5, the amount of crystallization inhibiting masterbatch used is too large. Although no floating fibers appear in Comparative Example 5, the crystallization ability is seriously affected, resulting in unsatisfactory demolding and affecting the processing and forming properties. In Comparative Example 6, the content of short-cut glass fibers is too high, resulting in floating fibers, and the crystallization ability is weakened, resulting in sticking films. In Comparative Example 7, no crystallization inhibiting masterbatch is added, and it can be seen that the floating fibers are serious and it is difficult to demold.
[0098] In Comparative Examples 8 and 9, no chlorine-containing compound and polyvinyl pyrrolidone were added respectively. Compared with Example 1, floating fibers appeared on the surface of the PA6 material, and the demolding phenomenon was not ideal, and the mechanical strength was also affected. In Comparative Example 10, a PA6 resin with a relatively large viscosity was used. Compared with Example 1, the flow rate of the PA6 resin was slower, making it difficult for the MXD6 nylon resin to play a role in dragging the chopped glass fibers. As a result, floating fibers appeared on the surface of the PA6 material prepared thereby, and the glossiness decreased.
[0099] The nylon and glass fiber mixed material in the prior art in Comparative Example 11 has higher tensile strength and flexural strength, but has floating fibers on the surface and is not easy to demold.
[0100] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A non-floating fiber easy demoulding reinforced PA6 material, characterized in that: The raw materials include the following parts by weight: 26.7-72.1 parts of PA6 resin, 20-50 parts of chopped glass fiber, 5-15 parts of MXD6 nylon resin, 0.4-0.8 parts of compound antioxidant, 0.5-1.5 parts of lubricant, and 2-6 parts of crystallization inhibition masterbatch; The crystallization inhibition masterbatch comprises the following raw materials in parts by weight: 60.6-64.5 parts of nylon resin, 4-5 parts of chlorine-containing compounds, 30-35 parts of polyvinyl pyrrolidone and 0.4-0.5 parts of compound antioxidant, wherein the chlorine-containing compounds comprise calcium chloride and lithium chloride in a mass ratio of 1:0.8-1; The mass ratio of the MXD6 nylon resin to the crystallization inhibition masterbatch is 2-2.5:1; The viscosity of the PA6 resin is 2.2-2.5, and the viscosity of the MXD6 nylon resin is 2.45-2.
7. The viscosity of the PA6 resin is lower than that of the MXD6 nylon resin. The chopped glass fibers are pre-treated as follows: The chopped glass fibers are immersed in an aqueous solution of a silane coupling agent, taken out, and dried to obtain pretreated chopped glass fibers; Dissolve polyvinylidene fluoride in a solvent to obtain a solution with a concentration of 50-55wt%, add a hyperdispersant and nano-silicon dioxide, and mix by ultrasonication to obtain a blended liquid, wherein the hyperdispersant is Lubrizol 17000; The blended liquid is evenly sprayed on the pre-treated chopped glass fibers and dried.
2. The non-floating fiber easy-to-release reinforced PA6 material according to claim 1, characterized in that: When pretreating the chopped glass fibers, the weight proportions of the raw materials are as follows: 40-50 parts of chopped glass fibers, 40-50 parts of an aqueous solution of a silane coupling agent, 5-10.5 parts of polyvinylidene fluoride, 3-6 parts of a hyperdispersant, and 4-8 parts of nano-silicon dioxide.
3. The non-floating fiber easy-to-release reinforced PA6 material according to claim 1, characterized in that: The lubricant is selected from at least one of silicone powder, modified ethylene bisstearamide and calcium stearate.
4. The non-floating fiber easy-to-release reinforced PA6 material according to claim 3, characterized in that: The lubricant comprises silicone powder and modified ethylene bisstearamide in a mass ratio of 1:0.875-1.
5. The non-floating fiber easy-to-release reinforced PA6 material according to claim 1, characterized in that: The compound antioxidant comprises antioxidant 1098 and antioxidant 168 in a mass ratio of 2-2.5:
1.
6. The method for preparing the non-floating fiber easy-to-release reinforced PA6 material according to any one of claims 1 to 5, characterized in that: The following steps are involved: The PA6 resin, MXD6 nylon resin, compound antioxidant, lubricant and crystallization inhibition masterbatch are mixed evenly, and the short-cut glass fiber is added from the side feeding port. After blending, extrusion, granulation and vacuum drying, the floating fiber-free and easy-to-demold reinforced PA6 material is obtained.
Citation Information
Patent Citations
Low-floating-fiber and high-impact-strength polyamide composite material
CN112552674A
Low-warpage easy-to-weld nylon composite material and preparation method thereof
CN116003999A